2004
DOI: 10.1007/s00232-004-0670-2
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Binding to Na+,K+-ATPase Relaxes Cell Attachment and Sends a SpecificSignal (NACos) to the Nucleus

Abstract: Abstract. In previous work we described a "P-->A mechanism" that transduces occupancy of the pump ( P) by ouabain into changes in phosphorylation, stimulation of mitogen-activated protein kinase (MAPK), and endocytosis of cell-cell- and cell-substrate-attaching molecules ( A), thereby causing a release of the cell from the monolayer. In the present work we try to understand the mechanism of this effect; whether, in order to trigger the P-->A mechanism, ouabain should block the pumping activity of Na(+),K(+)-AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
60
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 60 publications
10
60
1
Order By: Relevance
“…First, the down-regulation of ␣1 Na/K-ATPase might make it less effective for Na/K-ATPase to interact with and then inhibit cellular Src. This would increase basal Src and FAK activity and consequently promote epithelial cell proliferation, migration, and invasion (34,38,39). Consistently, we found that metastatic prostate cancer cells are highly sensitive to the addition of the Na/K-ATPase ␣1 mimetics, including ND1 (supplemental Fig.…”
Section: Discussionsupporting
confidence: 77%
“…First, the down-regulation of ␣1 Na/K-ATPase might make it less effective for Na/K-ATPase to interact with and then inhibit cellular Src. This would increase basal Src and FAK activity and consequently promote epithelial cell proliferation, migration, and invasion (34,38,39). Consistently, we found that metastatic prostate cancer cells are highly sensitive to the addition of the Na/K-ATPase ␣1 mimetics, including ND1 (supplemental Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Cell detachment and ␤-catenin translocation to the nucleus in the presence of 1 M of ouabain were shown recently in MDCK cells. The authors did not report whether MDCK cells in these experiments underwent EMT (12,37). Another study showed that a concentration of 1 M ouabain was toxic for MDCK cells (1).…”
Section: Discussionmentioning
confidence: 92%
“…22,29,30 The effect on TF expression preceded these morphological changes. A nonspecific action of cardiac glycosides on cell viability can be excluded, as LDH release was not enhanced; moreover, ouabain (10 Ϫ7 mol/L) is known to exert an antiapoptotic effect on human umbilical vein endothelial cells, 31 and to reduce VSMC death during up to 30 hours of treatment (10 Ϫ3 mol/L).…”
Section: Discussionmentioning
confidence: 97%